2014
DOI: 10.1139/cjce-2013-0416
|View full text |Cite
|
Sign up to set email alerts
|

Modeling agricultural land drainage under spring snowmelt conditions with DRAINMOD

Abstract: There are few computer models that can simulate winter freeze-thaw conditions and spring snowmelt hydrology for agricultural tile drained lands. DRAINMOD, which is used widely to simulate tile drainage flows, has not been extensively applied during colder periods in eastern Canada. This study analyzes the performance of DRAINMOD for surface runoff and subsurface drainage predictions in southern Quebec during spring snowmelt. The model was tested with five years of field data. DRAINMOD was found to be adequate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…DRAINMOD is a field-scale hydrologic model first developed by Skaggs R. W. [13] and widely applied in poorly drained agricultural lands [6]. It can simulate surface runoff, subsurface drainage, evapotranspiration (ET), infiltration and WTD (DRAINMOD 6.1).…”
Section: Drainmod Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…DRAINMOD is a field-scale hydrologic model first developed by Skaggs R. W. [13] and widely applied in poorly drained agricultural lands [6]. It can simulate surface runoff, subsurface drainage, evapotranspiration (ET), infiltration and WTD (DRAINMOD 6.1).…”
Section: Drainmod Descriptionmentioning
confidence: 99%
“…where ∆ is the change in the water-free pore space or air volume (cm), D is the lateral drainage (cm), ET is the evapotranspiration (cm), DS is the deep and lateral seepage (cm), F is infiltration (cm), P is the precipitation (cm), RO is the surface runoff (cm) and ∆S is the change in surface water storage (cm). By using the equations, subsurface drainage rates and surface runoff output can be obtained [6]. Infiltration is estimated using the Green-Ampt equation and deep seepage is estimated using Darcy's law.…”
Section: Drainmod Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Hooghoudt drainage equation is popular in 1D models (e.g. Mollerup et al, 2014;Morrison et al, 2014) and even in some 2D applications (Abbaspour et al, 2001), but it does not take into account the effect of unsaturated water flow on drain discharge (Yousfi et al, 2014). Mollerup et al (2014) showed that the modeling results were similar when using the Hooghoudt equation in 1D and the Darcy approach in 2D to simulate drain discharge.…”
Section: Parameterization Of 1d 2d and 3d Field Drainagementioning
confidence: 99%